From Farms to Factories and Firms : Structural Transformation and Labor Productivity Growth in Malaysia - Abdur Rahman, Amanina (World Bank, Washington, DC, 2020)
This study aims to provide a quantitative and integrated analysis of long-term structural transformation and labor productivity growth in Malaysia. Using data from the Department of Statistics Malaysia from 1987 to 2018 and decompositions that take account of the static and dynamic efficiency gains from labor reallocation, it documents that Malaysia has undergone structural transformation from an agriculture-driven to a services-driven economy. However, in contrast to common perceptions, the country's impressive growth in output per capita over the past three decades can largely be attributed not to its structural transformation but instead to sustained growth in within-sector labor productivity. At 3 percent, the contribution of between-sector reallocation of labor to growth in output per capita in Malaysia has been relatively low. Accordingly, together with efforts to spur the more productive reallocation of labor across sectors and positively affect the employment rate, the main policy challenge for Malaysia going forward will be to achieve sustainable labor productivity growth within various sectors.